Mechanical evaluation of canine sacroiliac joint stabilization using two short screws. Issue 7 (5th August 2022) - Hanlon, John; Hudson, Caleb C.; Litsky, Alan S.; Jones, Stephen C.
Abstract: Objective: To assess the feasibility and mechanical stability of sacroiliac (SI) joint stabilization using 2 short 3.5 mm cortical screws, each spanning an average of 23% of the width of the sacral body. Study design: Cadaveric experimental study. Sample population: Twenty‐four canine pelvis specimens. Methods: Pelvis specimens were prepared by disarticulation of the left SI joint and osteotomy of the left pubis and left ischium, and stabilized using a single long lag screw (LLS), 2 short lag screws (SLS) or 2 short positional screws (SPS). Computed tomography (CT) imaging was used to determine standardized screw lengths for each group and was repeated following implant insertion. Specimens were secured within a servohydraulic test frame and loaded through the acetabulum to simulate weight bearing under displacement control at 4 mm/min for 20 mm total displacement. Group mechanical testing data were compared. Results: Peak load, yield load, and stiffness were more than 2 times greater in both the SLS and SPS groups when compared with the LLS group. No mechanical difference was identified between the short‐screw groups. Conclusion: Sacroiliac luxation fixation using 2 short screws created a stronger, stiffer construct when compared with fixation using a single lag screw spanning 60% of the width of the sacral body. No mechanical advantage was observed between short screws inserted in positional vs. lag fashion. Clinical significance: Sacroiliac luxation fixation using 2 short screws creates a mechanically superior construct with a larger region of acceptable implant positioning and potentially reduced risk of iatrogenic injury compared with conventional fixation.